Innovation Capability of Learning Orientation Mediators on the Performance of Tourism Industry MSMEs - Santoso, R Tri Priyono Budi; Fettry, Sylvia; Hermawati, Adya; Bahri, Syamsul; Fatmawati, Endang; Ali, Shujahat (Jurnal Aplikasi Manajemen, 2024)
The aim of this research is to prove the influence of learning orientation on the innovation ability and performance of MSMEs. Innovation ability mediates the influence of learning orientation on the performance of tourism MSMEs in Greater Malang. A quantitative approach was used with 100 tourism MSME owners in Malang Raya, East Java, Indonesia. Using Structural Equation Modeling (SEM) analysis, it shows that learning orientation has an influence on innovation ability and MSME performance and innovation ability has an influence on MSME performance and innovation ability is able to mediate the relationship between learning orientation and the performance of tourism MSMEs in Malang Raya. Based on the research findings, suggestions are put forward that tourism MSME actors in Greater Malang must adapt to environmental changes so that future researchers can study the business environment and market orientation to improve the performance of tourism MSMEs in Greater Malang.